Physical and Chemical Roles of Metalworking Fluids in a Vibration-Assisted Tapping System - Takeshi NOGAMI; Ken NAKANO (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2007)
A vibration-assisted tapping system has been developed in which a piezoelectric-zirconate-titanate (PZT) oscillator applies small-amplitude vibrations to a workpiece and a torque transducer measures the time-evolving torque during the tapping process. To investigate the roles of metalworking fluids, four different metalworking conditions have been examined: without metalworking fluids (dry), with an additive-free fluid (base oil), with an oiliness-agent-containing fluid (fluid A), and with an extreme-pressure-agent-containing fluid (fluid B). The time evolutions of the tapping torque have been obtained for tapping M3 threads in S45C steel with varying vibration amplitudes, vibration frequencies, and tapping speed. It has been found that the present system decreases the tapping torque; in particular, a decrement of up to 14% in the tapping torque is obtained for fluid A using 800-Hz vibrations with an amplitude of 5 μm at a tapping speed of 3 rpm. Increments in the vibration amplitude and frequency lead to decrements in the tapping torque, but the effect of the vibration tends to fade with increasing tapping speeds. It appears that vibrations enhance not only the physical effects but also the chemical effects of metalworking fluids.